Israeli policies towards imports of manufactured goods - Richard Pomfret (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1974)
In this paper the policy of the Israeli government towards imports of manufactured goods is examined. This policy has passed throuth two distinct phases. In the 1950s quantitative restrictions on imports were enforced to stimulate domestic production of import substitutes. In the 1960s the deleterious effects of protectionist policies on resource allocation were recognized and the emphasis was changed in favour of import liberalization, i.e. the replacement of quantitative restrictions by tariffs and the eventual reduction of the tariffs. In recognition of the discontinuity of import policy the paper is divided into two parts reflecting the two phases.
Keywords: 330